Effects of Dietary Katuk Leaf Extract on Growth Performance, Feeding Behavior and Water Quality of Grouper Epinephelus coioides - Agus Putra A. S; Urip Santoso; Meng Chou Lee; Fan Hua Nan (Graduate Program of Syiah Kuala University, 2013)
Abstract - Plant-derived materials are believed as potential nutrient sources to be applied in aquaculture. Although many studies to assess the benefits of plant extracts have been conducted, however effects of dietary katuk (Sauropus androgynus L. Merr.) on growth performances, feeding behavior and water quality of grouper (Epinephelus coioides) are not well known. In this study, 25 grouper juveniles weighing 11.27 ± 2.53 g were reared into 100-L tank (60 x 50 x 35 cm) and cultivated for 70 days. The fish were divided into four groups in triplicate, and were offered diet without katuk extract (control), diet supplemented with 1% katuk extract (SAA); diet supplemented with 2.5% katuk extract (SAB) and diet supplemented with 5.0% katuk extract (SAC) twice daily. Statistical analyses showed that dietary katuk extract caused a significant (P 0.05) increase in growth rate and feed intake. The efficiency of feed was also significant when fish offered diets supplemented with 1% of katuk extract which indicated by a lower feed conversion ratio. However, no statistical differences were observed on the survival rate, condition factor, viscerosomatic index and hepatosomatic index. Observation on feeding behavior found that all treated fish consumed compounded diet just after provided into their tank and there were no abnormal behavior or any healthy problems during experimental periods. It demonstrated that application of katuk extract in fish diets is acceptable and can stimulate the fish appetites. In conclusion, our studies indicated that dietary katuk (Sauropus androgynus) extract can be applied in aquaculture to stimulate the growth and improve feed utilization.Keywords: Feed conversion ratio, feed utilization, plant extract, Sauropus androgynus.